Daclatasvir and reduced‐dose sofosbuvir: An effective and pangenotypic treatment for hepatitis C in patients with estimated glomerular filtration rate <30 mL/min. Issue 3 (27th February 2019) - Goel, Amit; Bhadauria, Dharmendra S; Kaul, Anupma; Verma, Prashant; Mehrotra, Mayank; Gupta, Amit; Sharma, Raj K; Rai, Praveer; Aggarwal, Rakesh
ABSTRACT: Aim: Sofosbuvir is a key agent for HCV treatment. It is not recommended for patients with chronic kidney disease (CKD) and estimated glomerular filtration rate (eGFR) <30 mL/min. We report real‐life experience of treating a cohort of CKD patients with eGFR <30 mL/min using daclatasvir and half‐daily dose of sofosbuvir. Methods: Adults patients who (i) had eGFR<30 mL/min and detectable HCV RNA and (ii) were treated with interferon and ribavirin free, DAA based regimens were included. All patients were treated with daily doses of daclatasvir 60 mg and sofosbuvir 200 mg. The planned duration of treatment was 12 weeks, except for 24 weeks in those with either clinical evidence of cirrhosis or on immunosuppressive drugs. The end‐points of the study were: (i) 12 weeks of follow‐up after treatment completion, (ii) treatment discontinuation, or (iii) death or loss to follow‐up. Results: Thirty‐six (88%) among 41 included patients (median [range] age: 48 [19–75] years; 25 [61%] male; genotype 1/3/4 were 17/ 22/2; cirrhosis 5) completed the treatment, two discontinued and three died during treatment. On an intention‐to‐treat basis, HCV RNA were undetectable at 4 weeks of treatment, treatment completion and after 12 weeks of follow‐up in 40/41 (97.6%), 37/41 (90.2%) and 37/41 (90.2%), respectively. None of the patients had a relapse. Conclusions: Daclatasvir and half‐daily dose of sofosbuvir was effective against genotype 1 and 3 HCV infection in patients with eGFR <30 mL/min. This combination could be a pangenotypic treatment option for such patients. Summary at a Glance: This is a real‐world report on the use of DAAs for pan‐genotypic HCV infection in patients with significant renal impairment in a resource constrained setting. It provides useful additional data for clinicians outside of clinical trial reports.